2006
DOI: 10.1099/mic.0.28383-0
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional analysis of the F0F1 ATPase operon of Corynebacterium glutamicum ATCC 13032 reveals strong induction by alkaline pH

Abstract: Corynebacterium glutamicum, a soil Gram-positive bacterium used for industrial amino acid production, was found to grow optimally at pH 7?0-9?0 when incubated in 5 litre fermenters under pH-controlled conditions. The highest biomass was accumulated at pH 9?0. Growth still occurred at pH 9?5 but at a reduced rate. The expression of the pH-regulated F 0 F 1 ATPase operon (containing the eight genes atpBEFHAGDC) was induced at alkaline pH. A 7?5 kb transcript, corresponding to the eight-gene operon, was optimally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
6
25
0
Order By: Relevance
“…WLY78 nifB promoter is apparently recognized by E. coli σ 70 RNA polymerase in vivo . These data concur with previous studies where promoters of gram-positive bacteria, for example, Bacillus stereothermophilus [22] and Corynebacterium glutamicum [23], were shown to be functional in E. coli .…”
Section: Resultssupporting
confidence: 92%
“…WLY78 nifB promoter is apparently recognized by E. coli σ 70 RNA polymerase in vivo . These data concur with previous studies where promoters of gram-positive bacteria, for example, Bacillus stereothermophilus [22] and Corynebacterium glutamicum [23], were shown to be functional in E. coli .…”
Section: Resultssupporting
confidence: 92%
“…Among them are genes encoding subunits of the succinate dehydrogenase, the F 1 F 0 -ATPase, and rRNA genes. For several of them the expression was shown to be dependent on the growth rate which is in agreement with a lower expression at pH 6 and pH 9 at which we observed lower growth rates than at neutral pH [10]. The evaluation of differential transcript and protein patterns by the comparison with targets of transcriptional regulators in C. glutamicum unraveled numerous regulatory modules that are activated during pH acclimatization.…”
Section: Discussionsupporting
confidence: 82%
“…The F 1 F 0 ATPase was found to function as a proton exporter under acidic conditions in Enterococcus hirae and its role in pH homeostasis in other bacteria was discussed [7,9]. In C. glutamicum the atp gene cluster encoding the F 1 F 0 ATPase was found to be transcriptionally induced at alkaline pH under the control of the sigma factor SigH and subsequent studies indicated that the expression is correlated with growth rate rather than the pH value of the medium [10,11]. Furthermore a putative cobalt transporter encoded by the gene cg1447 was found to be important under alkaline conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is an atpI gene that encodes a putative hydrophobic protein predicted to have 4 TMH. The AtpI protein sequence is not highly conserved across species [76]. In some instances atpI is under control of a separate promoter from the other atp genes [76], in some instances atpI is absent entirely [77] and in some instances atpI is absent but a different gene of unknown function takes its usual place [78].…”
Section: Overview Of Bacterial Atp Synthase Structure-functionmentioning
confidence: 99%
“…The AtpI protein sequence is not highly conserved across species [76]. In some instances atpI is under control of a separate promoter from the other atp genes [76], in some instances atpI is absent entirely [77] and in some instances atpI is absent but a different gene of unknown function takes its usual place [78]. Gay and Walker suggested a chaperone/assembly type of function for the AtpI protein when they first described the atpI gene [79].…”
Section: Overview Of Bacterial Atp Synthase Structure-functionmentioning
confidence: 99%